Analisis Komparasi Tiang Pancang dan Tiang Bor pada Gedung FEB UPN Veteran Jatim (EXTRAPOLASI, 2023)
Recently, have been applied widely in infrastructure in Indonesiam especially if the new building was built around another building. Therefore, bore pile is considered the most suitable for this case. In this research, the pile which ere previously in existing condition as group drilled piles were modified into single bore pile. The result of this study indicate that the use of single borepile is considered very safe in terms of bearing capacity, deflection and settlement